Filmer le travail à Peugeot Sochaux. Une approche comparative - Salvatore Maugeri (Images du Travail, Travail des Images)
This text sets out a comparative analysis of two documentaries – available on the internet – focused on Peugeot’s factories in Sochaux. The first one is titled « En passant par la Franche-Comté » (Throuh Franche-Comté), directed by Michel Boyer (1954 [1957 ?], 54’) ; the second one is titled « Avec le sang des autres » (With the blood of the others), directed by Bruno Muel (1974, 50’). Everything is different about these movies : the date of production, the ideological purposes, the financial and technical means implemented. By deciphering both documentaries meticulously, we will try to highlight the decisions taken by the directors regarding the storylines and the writing in the best interest of their project. Apology of the industrial genius of a family in the negation of human labor against socio-historical testimony of the damage related to the putting into work of the human resource of a whole region, that is the opposition. We will focus on disclosing the special cinematic devices og each director.